Impacts of iPad attributes, Lifestyles and media dependency on adoption of iPad and intensity of iPad usage in Mainland China - Li Xinpeng Kevin (International Telecommunications Society (ITS), 2012)
The goal of this exploratory research is to identify attributes that can distinctly characterize iPad and examine the predictive power of iPad attributes, lifestyles, media dependency, and demographics on adoption of iPad, iPad usage patterns and intensity of iPad usage. Using a snowballing sample, an online survey was conducted with 623 university students in Mainland China, among which 217 were iPad users and 406 were non-users. Results of regression analyses show that application affordances is one of the few important attributes influencing the likelihood of iPad adoption, iPad usage patterns and intensity of iPad usage. Regarding lifestyles, strivers were found to be associated with higher likelihood of buying iPad; experiencers were more engaged and active when using iPad; innovators tended to use iPad for utilities, information-seeking and communication more often than other users. Interestingly, owning other Apple products has a positive impact on purchasing iPad. Furthermore, among iPad usage patterns, in particular, utilities and information-seeking are significant predictors for Intensity of iPad usage, which proves to be the most important functionalities for iPad.
Keywords: 330; iPad attributes; Lifestyles; Media Dependency; Adoption of iPad; Intensity of iPad usage